Education of the mind and body from the physical standpoint - Failyer, Lois (My University, 1907)
Introduction: Education was formerly considered in a narrow sense, as it was thought of as only brain culture, and that the mind depended entirely upon the cultivation of the brain as if it were a distinct and independent part of the body. Now it is considered in a broader light, since the growth of the intellect depends upon the development of the nerves, muscles, viscera, and other organs as well as on the brain. However, physical education is still held to be as second to mental education. But the time will come when the two will be equal. Dr. D. A. Sargent says, "I maintain that the only rational method that will enable us to accomplish a perfect harmony is by placing mental and physical exercises on the same plane and by regarding every honest and faithful attempt toward physical improvement by the same recognition that we bestow upon the efforts to improve the mind." The object of all education is to develop the best type of citizens possible, in the best physical, mental and moral manner, attainable. Best physically, because without a sound body it is impossible to have the highest type of intellectual development; without a sound mind and body, it is impossible to have the best quality of moral development.
Citation: Failyer, Lois. Education of the mind and body from the physical standpoint. Senior thesis, Kansas State Agricultural College, 1907.
Morse Department of Special Collections
Keywords: Education; Physical Education; Mental Education; Theses